The Role of Domestic Debt Markets in Economic Growth : An Empirical Investigation for Low-Income Countries and Emerging Markets - Abbas, S. M. Ali (IMF Working Papers; Working Paper ;, 2007)
We develop a new public domestic debt (DD) database covering 93 low-income countries and emerging markets over the 1975-2004 period to estimate the growth impact of DD. Moderate levels of non-inflationary DD, as a share of GDP and bank deposits, are found to exert a positive overall impact on economic growth. Granger-causality regressions suggest support for a variety of channels: improved monetary policy; broader financial market development; strengthened domestic institutions/accountability; and enhanced private savings and financial intermediation. There is some evidence that, above a ratio of 35% percent of bank deposits, DD begins to undermine growth, lending credence to traditional crowding out and bank efficiency concerns. Importantly, the growth contribution of DD is higher if it is marketable, bears positive real interest rates and is held outside the banking system. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate.